Global Connectivity, Spatial Proximity, Multimodal Transport, and Polycentric Urban Regions: UAE Urban Development 2020 - 2030 - Brownson, John A. Jamil; Touq, Ahmad Bin; Almuraqab, Nasser A. Saif (International Journal of Membrane Science and Technology, 2023)
At a current world city scale, conurbations interweave complex multimodal systems of logistics, transport, and communications. As this process evolves into a global network of interconnected urban nodes. While diffusing globally, China’s One Belt One Road (OBOR) proposal creates an infrastructural framework for global exchange, analogous to the Ancient TransAsian links of Silk Road and Indian Ocean. Linked spatial dimensions and functional regions have always existed at different scales without any synchronized nomenclature for a grid with exact dimensional measurements. The global surface exists as a topological phenomenon of multi scalar dimensions covered by varied surface phenomena from earth to vegetation with fluid elements alternating in liquidity and flows. increasingly the world cities trend divides more advanced urban regions from less well viably connected territories, governments, industries, and commerce. Thus, the world has been experiencing an unequal distribution of trade and associated transport, logistics and handling facilities. In relation to global trade and transport tends to focus on the post-industrialized West and East and so underplays the role of other parts of the world system, including the MENASA (Middle East–North Africa–South Asia) region. In doing so, scholars discount a variety of spatial, morphological, environmental, historical, and socio-political urban patterns particular to these other regions and cities. This article addresses this oversight by examining the United Arab Emirates coastal conurbation (U.A.E.–CC, including Dubai–Abu Dhabi–Sharjah–Ajman), with its unique global positioning and political and economic conditions. The U.A.E.–CC is explored in relation to theories of the world/global city, the airport city or aerotropolis, and the polycentric urban region (PUR). The article demonstrates the emerging formation and potential of the U.A.E.–CC PUR, a member of a world-city network specializing as a transport hub and tourist destination and a global logistics center.